Study on Constructing Community - Based Tourism to Develop Source of Income in Kintamani Bangli Tourist Destination - BUDHIASA, Gede Sujana; WARKAMAMU, Thobby; SANTANU, Gede (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).02, 2019)
This paper aims to analyze influence of public policy towards Community-Based Tourism (CBT), members of community who get involved in tourism sector, social capital and CBT community. The study was conducted in Kintaman tourist destination in Bangli because UNESCO established Kintamani as one of the world heritage in 2016. This brought more visitors to Kintamani. Therefore, the researchers are interested in analyzing certain aspects that influence success of the tourist destination in the future. The study shows that public policy has positive influence towards CBT and public policy also has positive influence towards social capital. However, public policy does not have any influence towards Masyarakat Sadar Wisata (MSW). Entrepreneurship and MSW have positive influence towards social capital and social capital influences CBT. The study is one of few studies focusing on the role of social capital development to promote community-based tourist destination. This study will also investigate public perception on public policy and use both perceptions (social capital potential and public policy) to describe to what extent the public policy supports the social capital potentials and CBT.